Stability and permanence of a discrete-time two-prey one-predator system with Holling Type-III functional response. (December 2018) - Banerjee, Ritwick; Das, Pritha; Mukherjee, Debasis
Abstract: This paper deals with the complex dynamical behavior of a discrete-time two-prey one-predator system with Holling Type-III functional response, coupled with inter-specific competition among the prey due to dietary overlap and intra-specific competition among the predators. The existence and local stability criteria of the steady states of the system are analyzed and the conditions for permanent co-existence of the three species are obtained. Finally, using a suitable example, some numerical simulations are performed to illustrate the rich dynamics of the system.